Profil GC-MS Senyawa Metabolit Sekunder dari Jahe Merah (Zingiber officinale) dengan Metode Ekstraksi Etil Asetat, Etanol dan Destilasi - Yuspian Nur; Anom Cahyotomo; Nanda Nanda; Nurikhsan Fistoro (Jurnal Sains dan Kesehatan, 2020)
Red Ginger (Zingiber officinale) has a high economic value due to its use as a seasoning and also as traditional medicine. The test of phytochemical of vary Zingiber officinale rhizome showed that they have bioactive compounds. The bioactive compound was extracted using maceration techniques (using ethyl acetate and ethanol) and distillation. The aim of this study is to determine the profile of secondary metabolites compound and compare them from several technique of extraction. The results of GC-MS showed that the secondary metabolites compound from ethanol extract, ethyl acetate extract and distillation contains ar-curcumen, zingiberene,